Review article: the practical management of acute severe ulcerative colitis. Issue 4 (4th January 2016) - Seah, D.; De Cruz, P.
Summary: Background: Acute severe ulcerative colitis (ASUC) is a life‐threatening condition for which optimal management strategies remain ill‐defined. Aim: To review the evidence regarding the natural history, diagnosis, monitoring and treatment of ASUC to inform an evidence‐based approach to management. Methods: Relevant articles addressing the management of ASUC were identified from a search of MEDLINE, the Cochrane Library and conference proceedings. Results: Of ASUC, 31–35% is steroid‐refractory. Infliximab and ciclosporin salvage therapies have improved patient outcomes in randomised controlled trials. Short‐term response rates (within 3 months) have ranged from 40% – 54% for ciclosporin and 46–83% for infliximab. Long‐term clinical response rates (≥1 year) have ranged from 42%–50% for ciclosporin and 50–65% for infliximab. Short‐term and long‐term colectomy rates have been respectively: 26–47% and 36–58% for ciclosporin, and 0–50% and 35–50% for infliximab. Mortality rates for ciclosporin and infliximab‐treated patients have been: 0–5% and 0–2%, respectively. At present, management challenges include the selection, timing and assessment of response to salvage therapy, utilisation of therapeutic drug monitoring and long‐term maintenance of remission. Conclusions: Optimal management of acute severe ulcerative colitis should be guided by risk stratification using predictive indices of corticosteroid response. Timely commencement and assessment of response to salvage therapy is critical to reducing morbidity and mortality. Emerging pharmacokinetic models and therapeutic drug monitoring may assist clinical decision‐making and facilitate a shift towards individualised acute severe ulcerative colitis therapies.